Nicht-lineare Dynamik der HRV in Bezug zur kortikalen Aktivierung während einer fahrradergometrischen Dauerbelastung mit unterschiedlichen Trittfrequenzen - Gronwald, T.; Hoos, T.; Ludyga, S.; Hottenrott, K. (Herzfrequenzvariabilität: Methoden und Anwendungen in der Sportwissenschaft, Arbeits- und Intensivmedizin sowie Kardiologie. 7. Internationales HRV-Symposium am 4. März 2017 in Halle (Saale), 2018)
Following a holistic approach, measures of brain cortical activity in relation to exercise-induced changes in autonomic control will allow a more detailed exploration of complex control mechanisms of fatiguing exercise. Therefore, the purpose of the current study was to investigate the influence of exercise duration and cycling cadence on total variability and complexity of heart rate variability (HRV) in relation to cortical activity measured with electroencephalography (EEG).